A Broadband Bow-Tie Cavity-Backed Slot for Traveling-Wave Arrays in the Millimeter-Wave Band - Hernández Escobar, Alberto; Abdo-Sánchez, María Elena; Camacho-Peñalosa, Carlos (My University, 2019)
The use of bow-tie geometries to enhance the characteristics of a radiating element previously proposed by the authors is presented. The previous element consisted of a broadband cavity-backed slot in transmission configuration. The bow-tie shape of the cavity improves the bandwidth of the element and the bow-tie slot keeps constant the amount of power radiated. The structure is designed for the millimeterwave band. The enhancement of the element performance is shown through simulation results. A fractional bandwidth of more than 100% is achieved in the 70 GHz band, and the radiated power remains almost constant throughout 30 GHz of the bandwidth. These results show a great improvement over the original radiating element. The radiating structure has the ideal characteristics for building series-fed reconfigurable arrays for wide-band applications in the millimeter-wave band.
Keywords: Antenas-Congresos; Antenna; Bow-tie slot; Broadband radiating element; Cavity-backed slot; Millimeter-wave; Stripline; Traveling-wave